Optimization of propulsion in rowing - Schaffert, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The reduction of intra-cyclic fluctuations in propulsion speed has been proposed as a means to enhance the efficiency of propulsion in rowing. Boat acceleration was found to be a reliable measure for the effectiveness of the rowing stroke as it is the direct result of all forces acting on the system (boat and rower) at any given moment (the sum of stretcher force, handle force, frictions, etc). By coordinated movements of the athletes, intra-cyclic occurring variations in boat speed can be reduced particularly during the propulsive-critical phase of the rowing cycle (recovery) (Kleshnev, 2009). Since there is evidence that listening to complex sound sequences improves the precision in motor control for an exact timing and regulation of movement-patterns (Thaut, 2008), an auditory feedback system (Sonification in rowing) has been developed for technique training in on-water rowing. The additionally provided acoustic information, produced synthetically by sonification, maps the boats` acceleration data to sound to monitor changes in data. Empirical results from investigations with elite athletes in on-water training and theoretical insights obtained in the context of this application will be presented. More specifically, it will be shown how the presentation of acoustic feedback can affect the time-structure of the rowing cycle by providing detailed information about its characteristic phases.